Βιβλιοκριοία: The Orthodox Church in the Arab World 700-1700. An Anthology of Sources. Edited by Samuel Noble and Alexander Treiger (Northern Illinois University Press, 2014) - SAHAS, Daniel (Byzantina Symmeikta, 2018)
The Orthodox Church in the Arab World 700-1700. An Anthology of Sources. Edited by Samuel Noble and Alexander Treiger (Northern Illinois University Press, 2014) .